Scalable multimedia streaming model in heterogeneous networks. (15th November 2007) - Itaya, Satoshi; Enokido, Tomoya; Takizawa, Makoto
In a Peer-to-Peer (P2P) overlay network, a large number and various types of peers are cooperating by exchanging multimedia contents. Here, multimedia streaming is a key technology to realise multimedia applications. In multimedia streaming applications, multimedia contents are required to be efficiently delivered to processes in a real-time manner. Some contents peer may not send packets at a required rate and a communication channel may not support enough Quality of Service (QoS). In this paper, we newly discuss a Heterogeneous Asynchronous Multi-Source Streaming (HAMS) model where multiple contents peers transmit packets of a multimedia content to a requesting leaf peer to realise high reliability and scalability.